Réseaux de télécommunications et aménagement des territoires - Bruno Moriset (Unité Mixte de Recherche 8504 Géographie-cités, 2010)
Since the advent of the Internet, the digital divide has become a popular issue. “Bridging the broadband gap” has been the focus of many national and local policies throughout the world. In France, like in similar countries, public and private investments, ad hoc regulation, and the implementation of local loop unbundling have brought broadband access to the Internet to nearly the full country, without regard of location. However, since the middle of the 2000s, the emergence of ultra-high broadband services on a fiber optic local loop – FTTH, for fiber to the home – is threatening to generate a dramatic upheaval of the “net economy”, and to create a territorial “digital divide 2.0”. FTTH is a disruptive, technology, and the new gap would be more harmful and much costlier to bridge. After surveying the decline of digital divide 1.0, this paper elaborates on the geographic and public policy dilemma which is carried on by the unavoidable, but spatially uneven development of optic fiber.